2021
DOI: 10.1002/mar.21564
|View full text |Cite
|
Sign up to set email alerts
|

Waiting for a download: The effect of congruency between anthropomorphic cues and shopping motivation on consumer patience

Abstract: Consumers tend to be impatient during an online wait (e.g., waiting for webpages to download), which may decrease their satisfaction with online retailers. The current research addresses this important issue by identifying a simple and viable strategy to boost consumer patience: the presence of anthropomorphic cues on the download interface. In particular, we postulate a matching effect between anthropomorphic cues and shopping motivation on consumer patience, such that hedonic (vs. utilitarian) consumption be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 68 publications
2
8
0
Order By: Relevance
“…They also rated a three‐item measure of perceived enjoyment (e.g., “I feel enjoyable when I am trying the pen”; α = 0.87) and a three‐item measure of perceived autonomy (e.g., “I believe that I had a choice over how to use the product”; ɑ = 0.77) adopted from the Intrinsic Motivation Inventory (Ryan et al, 2006). Pervious research (Chen et al, 2021) implies that marketing strategy, such as sophisticated (simple) brand ritual in our research, that is consistent with a sincere (an exciting) brand can increase consumer purchase. To address this possibility that brand consistency may mediate the interaction effect of brand ritual and brand personality on consumer purchase, participants rated perceived brand consistency with three items (e.g., “the new pen seems to reflect that of Sheko company”; ɑ = 0.90; Sundar & Noseworthy, 2016).…”
Section: Methodssupporting
confidence: 79%
See 1 more Smart Citation
“…They also rated a three‐item measure of perceived enjoyment (e.g., “I feel enjoyable when I am trying the pen”; α = 0.87) and a three‐item measure of perceived autonomy (e.g., “I believe that I had a choice over how to use the product”; ɑ = 0.77) adopted from the Intrinsic Motivation Inventory (Ryan et al, 2006). Pervious research (Chen et al, 2021) implies that marketing strategy, such as sophisticated (simple) brand ritual in our research, that is consistent with a sincere (an exciting) brand can increase consumer purchase. To address this possibility that brand consistency may mediate the interaction effect of brand ritual and brand personality on consumer purchase, participants rated perceived brand consistency with three items (e.g., “the new pen seems to reflect that of Sheko company”; ɑ = 0.90; Sundar & Noseworthy, 2016).…”
Section: Methodssupporting
confidence: 79%
“…Pervious research (Chen et al, 2021) implies that marketing strategy, such as sophisticated (simple) brand ritual in our research, that is consistent with a sincere (an exciting) brand can increase consumer purchase. To address this possibility that brand consistency may mediate the interaction effect of brand ritual and brand personality on consumer purchase, participants rated perceived brand consistency with three items (e.g., "the new pen seems to reflect that of Sheko company"; ɑ= 0.90; Sundar & Noseworthy, 2016).…”
Section: Methodssupporting
confidence: 78%
“…This result is similar to recent findings suggesting anthropomorphism has an empathy‐helping underlying psychological mechanism that can make unattractive products more attractive (Chen, Razzaq, et al, 2021). This moderating effect may also be explained by the different motivations that drive the purchase of vice and virtue products, as purchase motivations have been shown to interact with anthropomorphic cues to explain consumer behavior (Chen, Wei, et al, 2021). We also found an unexpected influence of vice products on attitudes and loyalty to the dump bin.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, previous research has largely revealed the positive consequences of anthropomorphism on consumers’ judgments and behavior. For example, incorporating anthropomorphic cues in the designs of artificial intelligence can improve adoption intention (Letheren et al, 2021; Moriuchi, 2021; Whang & Im, 2021), presenting anthropomorphic cues in advertisement enhances consumer evaluation (Do et al, 2021; Han et al, 2019; Lee & Oh, 2021), and incorporating similar cues in online web design increases consumer patience (S. Chen et al, 2021). Consumers also express greater liking toward anthropomorphized products and brands compared with nonanthropomorphized ones (Aggarwal & McGill, 2007, 2012), even when they are unlovely sometimes (e.g., food of ugly shape) (T. Chen et al, 2021; Shao et al, 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%